An afrocentric critique of China’s Foreign Policy towards Africa : case studies of Angola and the Democratic Republic of Congo, 2010-2020 - Rapanyane, Makhura Benjamin (My University, 2023)
The foreign policy of China which is also globally known as the People’s Republic of China (PRC) has in the recent past become a substantial subject of both policy and academic debates. This is mostly due to the attention that China has given to the African continent. The attention expanded through the formation of the Forum on China-Africa Cooperation (FOCAC) in the early 2000s. It is incontestable that FOCAC has been driving China-Africa political and economic relations, ultimately becaming the second biggest economy globally after the United States of America (USA). Contextually, this study has employed a comparative case study design to critique China’s foreign policy towards the African continent. This case study design has utilised both Angola and the Democratic Republic of Congo (DRC) as test cases to critique the post-2010 foreign policy of China towards the African continent. This was done through critical analysis of China’s Africa policy, and therefore, unearthing China’s global engagement (herewith referred to as foreign policy) with reference to both Angola and the DRC. To this end, the current study provides historical sensibility by locating China’s global engagement with Africa, specifically the context of Angola and the DRC as far back as the colonial period. The exceptional acknowledgement of historicity in the current study extensively drew from the idea that the past customarily informs a vibrant premise for the understanding of the present and the future. In the current study, the researcher has championed the adoption and use of the Afrocentric theory as a replacement of the mainstream theories in interpreting the general foreign policy of China towards the African continent. The adoption and the use of this theoretical lens in the study has been informed by its capacity to accentuate and underline China’s international relations with both Angola and the DRC. A scholarly understanding of China’s foreign policy on Angola and the DRC can be achieved when such analysis and interpretations are accurately located within the African continental context. Equally significant are the study’s objectives which are attained through the use of interviews and document review. This is a type of qualitative research approach that appreciates the use of interviews and document review to generate relevant primary and secondary information in the quest to answer the study’s main question. In consideration of the study’s comparative case study design, the foundational highlights from the study are that: China premises its international relations with African countries (Angola and the DRC) on several factors that include access to oil, copper, diamonds, cobalt, and other important mineral resources-for-infrastructural-loans. In addition, both Angola and the DRC’s slight stable economic and political environments have continued to play an important role in their continued engagement with China. This is the case, although there are various Chinese Multinational Corporations (MNCs) and State-Owned Enterprises (SOEs) with operations in both Angola and DRC that are still incompetent in the practice of Corporate Social Responsibility (CSR). Overall, the CSR concept should precede all the operations of Chinese companies in Angola and the DRC economic stakeholders.
Thesis (Ph.D. (International Politics)) -- University of Limpopo, 2023
Keywords: Afrocentricity; Angola; Democratic Republic of Congo; China; Corporate social responsibility; Belt and road initiative; Forum on China-Africa cooperation; Infrastructural-loans-for-minerals; Oil; Copper; Cobalt; Credit lines policy; Commercial policy; International relations; Social responsibility of business; Foreign trade promotion; Afrocentrism; International relations -- History